The Role of Expenditures in Predicting Adequate Yearly Progress for Special Needs Students in Ohio - Korrin M. Ziswiler; Barbara M. De Luca; Luke J. Stedrak (Educational Considerations, 2013)
Although there exists a large body of research concerning the relationship between expenditure and student achievement, a lack of research exists analyzing this relationship as it pertains specifically to students with disabilities.
Keywords: expenditures; predicting; progress; Ohio; K-12 Students; schools; special needs; special education; academic; performance; research